2016
DOI: 10.17239/jowr-2016.07.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Language of Citation across Discipline and Experience Levels: An Automated Dictionary Approach

Abstract: source use of new kn formal ch know from reports on and levels sixteen pa (Compute Social Sci participan one's own Keywords , A. (2016). Rhet f Writing Researc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…A different kind of analysis can be achieved when close analysis of discourse is preceded by computational corpus analysis. Computational corpus analysis can directly support close analysis either by imposing a rhetorical framework on common language patterns, as in the Carnegie Mellon studies using Docuscope (e.g., Kaufer & Ishizaki, 2011; Kaufer et al, 2016) or by relying on the computational analysis to reveal patterns of discourse that can then be sampled for close analysis (e.g., Boettger & Wulff, 2014; Carradini, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A different kind of analysis can be achieved when close analysis of discourse is preceded by computational corpus analysis. Computational corpus analysis can directly support close analysis either by imposing a rhetorical framework on common language patterns, as in the Carnegie Mellon studies using Docuscope (e.g., Kaufer & Ishizaki, 2011; Kaufer et al, 2016) or by relying on the computational analysis to reveal patterns of discourse that can then be sampled for close analysis (e.g., Boettger & Wulff, 2014; Carradini, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The ability to cross-reference the content of texts with metadata (in this case, metadata being the outcome of voting on the approval of a drug as a result of the meeting) led to an insight on how the content of the meetings may have affected the outcome of voting. Researchers can conduct this type of cross-referencing outside medical documentation for proposed policy documents concerning issues of technical communication interest that may have a range of outcomes (passed, tabled, returned to committee, rejected), as well as emerging proposal genres such as crowdfunding campaigns (Ishizaki, 2016) that have largely binary outcomes.…”
Section: The Possibilities Of Corpus Analysis In Technical Communicationmentioning
confidence: 99%
“…An example of a question of kind comes from David Kaufer et al (2016), who took a corpus analytic approach to studying citation practices among academics. This work built on research by Andreas Karatsolis (2016) and demonstrated how corpus analytic techniques allow researchers to supplement and guide close textual analysis.…”
Section: Observational Questionsmentioning
confidence: 99%
“…Technical communicators could help online communities work as communities by finding trends in questions and solutions and from that trend analysis find points at which to intervene with targeted documentation. To support this work, technical communicators should develop skills in analyzing and mining text (see Geisler, 2003; Kaufer, Ishizaki, & Cai, 2016) in order to develop awareness of the discourse patterns that signal different kinds of questions and purposes for asking. Individual questions can easily get lost in the rush of conversation in an online forum, but as the research here demonstrates, users often relied on similar kinds of language to signal types of questions.…”
Section: Description Of Operationsmentioning
confidence: 99%